Mercury, lead and cadmium levels in the urine of 170 Spanish adults: A pilot human biomonitoring study - Castaño, Argelia; Sánchez-Rodríguez, Jinny E.; Cañas, Ana; Esteban, Marta; Navarro, Carmen; Rodríguez-García, Ana C.; Arribas, Misericordia; Díaz, Gema; Jiménez-Guerrero, José A. (International journal of hygiene and environmental health, 2012)
Human biomonitoring is a well-recognized tool for estimating the exposure of human populations to environmental pollutants. However, information regarding biomarker concentrations of many environmental chemicals in the general population is limited for many countries. The Spanish Environment Ministry has recently funded a human biomonitoring study on the Spanish general population. This study aims to determine reference levels for several biomarkers, especially heavy metals, persistent organic pollutants (POPs) and cotinine, in urine, whole blood, serum and hair, and will involve 2000 volunteers throughout Spain. Samples were taken during 2009–2010 and analyses are currently underway. The results presented herein were obtained in a pilot study carried out in the Madrid region. The study group comprised 170 volunteers, of which 79% were female and 21% male (age: 23–66 years). All participants were asked to complete a questionnaire regarding diet and living habits and provides a morning urine sample. The geometric means for total mercury (Hg), lead (Pb) and cadmium (Cd) were 1.23, 1.11 and 0.25μg/g creatinine, respectively. Levels of Pb and Hg were higher than those reported for the general population in the USA and Germany, whereas Cd was in the same range (CDC, 2009; Becker et al., 2003). The values reported here are similar to those reported in other Spanish studies.